6-4x=7x-9x+6

Simple and best practice solution for 6-4x=7x-9x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-4x=7x-9x+6 equation:


Simplifying
6 + -4x = 7x + -9x + 6

Reorder the terms:
6 + -4x = 6 + 7x + -9x

Combine like terms: 7x + -9x = -2x
6 + -4x = 6 + -2x

Add '-6' to each side of the equation.
6 + -6 + -4x = 6 + -6 + -2x

Combine like terms: 6 + -6 = 0
0 + -4x = 6 + -6 + -2x
-4x = 6 + -6 + -2x

Combine like terms: 6 + -6 = 0
-4x = 0 + -2x
-4x = -2x

Solving
-4x = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-4x + 2x = -2x + 2x

Combine like terms: -4x + 2x = -2x
-2x = -2x + 2x

Combine like terms: -2x + 2x = 0
-2x = 0

Divide each side by '-2'.
x = 0

Simplifying
x = 0

 

See similar equations:

| X-5(2-x)=6x | | 75(n+3)=9 | | graphy=5x-3 | | 72-4x=10x+16 | | .83x-3=12 | | -25-4x=5-10x | | 5c-7=2c-1 | | (5-6i)(2+3i)= | | 123-6x=3x+15 | | (3x+9)(4x-2)=0 | | -5x+.6=2.8 | | 1x-3x-40=0 | | -18-10x=9x+20 | | 4b+8.2=46.8 | | 4x-5=x+1 | | 6-9x=98-37x | | 17+3(z-2)-11z=-7(z+2)+14 | | 1x+8x+24=9 | | 68-2x=7x+16 | | 1x-10x+9=-3x-1 | | 2(5x+3)+22=25x-2 | | C(q)=25+3q+2q^2 | | 4(y-7)=2y-38 | | 12x+6=7x+21 | | 2z+4=5z-8 | | 4W^2+12W+9=121 | | x^2+4x+6=0 | | 3x+80=9x+14 | | 5x+37=14x-44 | | 2x-1=11x-64 | | 3X^2=75 | | 8+10x=35+x | | 3p+5=p+1 | | p^2-14p+49=0 | | x+(x*y)=10 | | P^2-18P+81=0 | | x+(x*0.34)=12 | | 5y+3=4y+11 | | X^2-5X=0 | | 6x+3=2x+39 | | (6+x)(3x+11)= | | 2x-5=x-10 | | Y=X^2+2X-5 | | x^2-3x-4=0 | | -7(w-2)=5(3-w) | | 6x+11x=1+11 | | 3x+5=29 | | 3X^2-45=0 | | 8p+10p+4p+19p= | | 3m-9m=3 | | 42-6x+x=17 | | 1x=25*12 | | (4x-14)(3x+12)= | | 3x=12*13 | | X^2-49=0 | | 6x*12= | | -4-a=11 | | 2x-6=6x+14 | | 7x*12=15 | | 6+x=-2x-6 | | 2ab+2= | | 2(2x-5)=10 | | 16-b=24 | | -3(2-4x)=10x | | 4(3+2)=32 |